Tooth discoloration effects of calcium silicate based barrier materials used in revascularization and treatment with internal bleaching - Makbule Bilge Akbulut; Arslan Terlemez; Melek Akman; Begum Buyukerkmen; Mehmet Burak Guneser; Ayce Unverdi Eldeniz (Elsevier, 2017)
Background/purpose: Usage of barrier materials is an important step in revascularization procedure. One of the undesired properties of these barrier materials is to cause coronal tooth discoloration. The aim of this inÂ vitro study was to evaluate the tooth discoloration induced by ProRoot MTA (PMTA), Biodentine, and MM-MTA, as well as the efficacy of internal bleaching on this discoloration. Materials and methods: Forty-two maxillary incisor teeth were prepared. Triple antibiotic paste (TAP) was placed in the root canals and incubated for 3 weeks. After removing the TAP, blood embedded spongostans were inserted into the root canals, and PMTA, Biodentine, or MM-MTA was placed over them. The teeth were incubated for 4Â weeksÂ at 37Â Â°C; then, the internal bleaching agent was sealed for one week. The tooth color was measured throughout the study and the color change values (ÎE) of each specimen were calculated, and the data was statistically analyzed using the one-way ANOVA and Tamhane's T2 tests. Results: The TAP significantly decreased the luminosity of the teeth (pÂ <Â 0.05); however, no significant differences were observed between the tooth discolorations induced by the PMTA, Biodentine, and MM-MTA (pÂ >Â 0.05). The teeth in the Biodentine group were more whitened than those of the PMTA and MM-MTA groups (pÂ <Â 0.05). Conclusion: Although the PMTA, Biodentine, and MM-MTA caused similar color alterations in the teeth, more bleaching was observed on those teeth discolored using TAPÂ +Â bloodÂ +Â Biodentine. Keywords: dental materials, endodontics, revascularization, tooth bleaching